Surgical sequence, timing and volume, and variation in dento‐facial outcome, speech and secondary surgery in children with unilateral cleft lip and palate: The Cleft Care UK Study. (19th October 2022) - Slator, Rona; Perisanidou, Lydia I.; Sell, Debbie; Sandy, Jonathan; Ness, Andrew R.; Wills, Andrew K.
Abstract: Objectives: To estimate both the association of surgical variables in complete unilateral cleft lip and palate (cUCLP) in the UK with outcomes at age 5 years, and the association of secondary speech surgery, volume of surgery, and surgeon with the same outcomes. Setting and Sample Population: The Cleft Care UK study, a cross‐sectional study of 268 5‐year‐olds, born from 2005 to 2007, with cUCLP. Materials and Methods: Information on surgical variables was extracted from a standardized questionnaire. Dento‐facial outcomes were derived from dental study casts of dental arch relationships. Three speech outcomes – intelligibility, structure and articulation – were derived using the Cleft Audit Protocol for Speech‐Augmented tool. Results: Surgical and outcome data were available for 211 (79%) children from all cleft centres in the UK. Later soft palate surgery was associated with a 17% increased chance of a poor intelligibility score ( P = .02), and high volume surgery with a 249% increased chance of a good articulation score ( P = .01). There were no between surgeon effects identified. No association between the surgical variables examined and dento‐facial outcome, or secondary speech surgery by the age of 5 years were found. Conclusion: This study found associations between surgical variables and speech outcomes at 5 years of age, but not between surgical variables and dento‐facial outcome, nor between surgical variables and secondary speech surgery. High surgical volume should be maintained, and any changes towards later surgery monitored for changes in speech outcome.